PENGARUH MEDIA SOSIAL TERHADAP WAWASAN KEBANGSAAN MAHASISWA PPKN UNIVERSITAS LAMPUNG - Primawitha, Intan; Mona Adha, Muhammad; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of social media on the national insight of students in the Pancasila and Citizenship Education (PPKn) Study Program at the University of Lampung. This study used quantitative methods with a descriptive approach. The sample size was 76 respondents, determined using simple random sampling. Data collection techniques used questionnaires and interviews, while data analysis used simple linear regression. Based on the results of calculations and hypothesis testing conducted by researchers regarding the influence of social media on the national insight of Civics (PPKn) students at the University of Lampung, the results showed that social media (Variable X) had an effect on national insight (Variable Y) of 30.9%. The results indicate that social media influences the national insight of Civics (PPKn) students at the University of Lampung. The use of social media carries the risk of triggering the spread of hoaxes and content that undermines national unity. However, social media also has a positive impact in influencing national insight, especially among students. Through participation, interaction, sharing of national content, and various types of educational content on social media, students can learn about and learn about various national issues and strengthen their understanding of the values of Pancasila and diversity. Based on this, it can be concluded that social media contributes to shaping national insight among Civics (PPKn) students at the University of Lampung.